2020
DOI: 10.35709/ory.2020.57.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Land use efficiency and productivity of rice (Oryza sativa) under various irrigation regimes and intercropping system

Abstract: A field experiment was conducted at Tamil Nadu Rice Research Institute, Aduthurai to assess the land use efficiency and productivity of rice under intercropping system. Treatments consisted of six irrigation regimes viz., IW (depth of irrigation water) / CPE (Cumulative pan evaporation) ratio 1 up to harvest, IW/CPE 0.75 up to 60 days thereafter IW/CPE 1, IW/CPE 0.75 up to 60 days thereafter IW/CPE 1.25, IW/CPE 0.75 up to 60 days thereafter IW/CPE 1.50, IW/CPE 1 up to 60 days thereafter IW/CPE 1.25 and IW/CPE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…High level of dry matter production and efficient translocation of photosynthates from source to sink might be responsible for producing an increased level of yield. (Subramanian et al, 2020). This result clearly indicated that irrigation with lesser IW/CPE during early stages followed by higher IW/CPE during later stages proved to be the irrigation strategies for the aerobic rice system.…”
Section: Irrigation Scheduling and Intercrop Practice On Yieldmentioning
confidence: 71%
See 1 more Smart Citation
“…High level of dry matter production and efficient translocation of photosynthates from source to sink might be responsible for producing an increased level of yield. (Subramanian et al, 2020). This result clearly indicated that irrigation with lesser IW/CPE during early stages followed by higher IW/CPE during later stages proved to be the irrigation strategies for the aerobic rice system.…”
Section: Irrigation Scheduling and Intercrop Practice On Yieldmentioning
confidence: 71%
“…So, to increase the farm productivity and overall income for the farmers, a short duration suitable crop was introduced as intercrop. Intercropping in rice increases the productivity, profitability, and effective utilization of soil, water, nutrients and sunlight compared to sole crop (Subramanian et al, 2020). Thus, it is believed that efficient utilization of resources results in yield advantages.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to aerobic rice offers the new scope to introduce intercrops on par with other arable crops. Growing of short duration pulses in-between the aerobic rice is the recent advancement to fulfil the requirement of pulses as well as food grains without any reduction of the agricultural area (Subramanian et al, 2020). Keeping this in view, the present study was carried out to study on irrigation scheduling and intercropping on growth and yield of aerobic rice.…”
Section: Issn: 2319-7706 Volume 9 Number 10 (2020)mentioning
confidence: 99%